Novel mutation in the SOD1 gene in a patient with early‐onset, rapidly progressive amyotrophic lateral sclerosis. Issue 6 (5th September 2017) - Okazaki, Masahiro; Suzuki, Hidekazu; Takahashi, Yuji; Ishiura, Hiroyuki; Goto, Jun; Hirano, Makito; Saigoh, Kazumasa; Nakamura, Yusaku; Naruse, Hiroya; Mitsui, Jun; Tsuji, Shoji; Kusunoki, Susumu
Abstract: Genetic mutations have been found in many familial cases of amyotrophic lateral sclerosis (ALS), and 11% of sporadic cases. The most common causative gene in Japan is the SOD1 gene, encoding Cu, Zn superoxide dismutase, a radical scavenger. We report a 25‐year‐old man who had rapidly progressive sporadic ALS with a novel mutation, Gly147Ala, in this gene. Several missense mutations at this residue have been reported in patients with sporadic and familial ALS, among whom the onset age of the present patient was youngest. He had severe weakness of four limbs, with severe respiratory and bulbar involvements within 8 months. Recently, the radical scavenger, edaravone, has been approved as a medicine to treat ALS in Japan. Accumulation of patients like the present patient might be important for immediate diagnosis and treatment of patients who have sporadic ALS with mutations in causative genes.